Forkhead Box Protein-3 Gene Expression of Purified Human Peripheral Blood Mononuclear Cells Treated with Methicillin-Resistant Staphylococcus aureus-Somatic Antigens and Hepatitis B Virus Vaccine - Entidhar A. Hadi; Mohammad A. K. Al-Saadi; Kaiser N. Madlum (Medical Journal of Babylon)
Background: Optimal hepatitis B virus (HBV) vaccine efficacy linked to producing systemic and mucosal antibodies and cellular immunological memory requires a complete set of immunological responses. Numerous variables affect how strong the immunological response is important variables include the vaccine’s kind and any additional adjuvants, which can dramatically enhance antigen presentation and cell activation. Objectives: This study aimed to illustrate the purified human peripheral blood mononuclear cells’ immunological response against somatic antigens of methicillin-resistant Staphylococcus aureus (MRSA) and to study the immunodulatory effect of HBV antigens on this immune response represented by gene expression of forkhead box protein-3 (FOXP3) as a regulatory gene for immune cells. Materials and Methods: Case‐control research was conducted on 75 peripheral blood mononuclear cells (PBMCs) samples. This work involved five experimental groups each group involving 15 samples. Group I involves separated PBMCs (1 × 106 cells/mL) alone as a control; Group II involves PBMCs stimulated with killed somatic MRSA antigen; Group III of PBMCs were stimulated with HBV vaccine only; Group IV involves PBMCs pretreated with HBV vaccine for 48 hr, and then with killed somatic MRSA antigen. Group V involves PBMCs stimulated with mixed of killed somatic MRSA antigen and HBV vaccine. The immune response against MRSA somatic antigens was assessed by the genetic parameter was done to detect the level of FOXP3 mRNA gene expression by real-time polymerase chain reaction (PCR). Results: The results of relative gene expression in the (P < 0.05) FOXP3 gene showed that the mean concentration of FOXP3 gene expression level was significantly increased in Group II, Group III, Group IV, and Group V, respectively, as compared to Group I. Conclusion: MRSA-somatic antigens and HBV vaccine are significantly increased the regulatory FOXP3 gene expression as an indicator for increasing the immune response.